2015
DOI: 10.4269/ajtmh.14-0653
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into Circulating Cytokine Dynamics During Pregnancy in HIV-Infected Beninese Exposed to Plasmodium falciparum Malaria

Abstract: Abstract. We investigated the circulating plasma levels of Th1-(Interleukin-2 [IL-2], tumor necrosis factor-α [TNF-α], interferon-gamma [IFN-γ]) and Th2-type (IL-4, IL-5, IL-10) cytokines in human immunodeficiency virus (HIV)-infected pregnant women living in a malaria-endemic area. We analyzed samples from 200 pregnant women included in the prevention of pregnancy-associated malaria in HIV-infected women: cotrimoxazole prophylaxis versus mefloquine (PACOME) clinical trial who were followed until delivery. Cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Cord blood IP-10 levels of Kenyan neonates in our study were similar to the lower placental IP-10 levels of Malawian HIV infected non-transmitter pairs (cord blood cytokines were not measured in this study). Multiple studies have shown that Pf infection in pregnancy is associated with adverse outcomes and elevated pro-inflammatory cytokines/chemokines (7175). Few, however, have shown differences between maternal plasma levels at delivery and cord blood levels.…”
Section: Discussionmentioning
confidence: 99%
“…Cord blood IP-10 levels of Kenyan neonates in our study were similar to the lower placental IP-10 levels of Malawian HIV infected non-transmitter pairs (cord blood cytokines were not measured in this study). Multiple studies have shown that Pf infection in pregnancy is associated with adverse outcomes and elevated pro-inflammatory cytokines/chemokines (7175). Few, however, have shown differences between maternal plasma levels at delivery and cord blood levels.…”
Section: Discussionmentioning
confidence: 99%
“…Malaria and HIV are 2 of the most common and important health problems in sub-Saharan African countries, and pregnant women are particularly a vulnerable group (21). In pregnancy, the body undergoes modulation of pro-inflammation responses to ensure fetal survival (22). These adjustments may decrease maternal immune defenses and promote infections (17).…”
Section: Discussionmentioning
confidence: 99%
“…These adjustments may decrease maternal immune defenses and promote infections (17). HIV infection may impair immunity to malaria by altering cytokine profile Effect of malaria on the CD4 count and the tested cytokines among pregnant women (22). A number of factors have been reported to influence cytokine levels in an individual (23).…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation between IL-6 and TNF-α was also observed in HIV seropositive pregnant women with malaria coinfection. Further studies have indicated that acute malaria can also increase cytokine production which could subsequently lead to viral replication and immunological interactions [9,25]. In HIV infection, molecular redox balance is disturbed in CD4 + T cells which are accompanied by severe immune dysfunction thus, potentiating HIV replication.…”
Section: Discussionmentioning
confidence: 99%
“…is can easily occur due to reduced immunity [5] which also enhances coinfections such as malaria especially in places of high endemic transmission [6]. Reports have shown evidence of increased risk of placental malaria in HIV-infected pregnant women [7], which can grossly reduce their immunity to malaria infection leading to modulation of circulating cytokines [8] with synergistic exposure to adverse pregnancy outcomes [9].…”
Section: Introductionmentioning
confidence: 99%